Processional melodies in the Old Hispanic rite. Issue 2 (October 2021) - HORNBY, EMMA; ANDRÉS FERNÁNDEZ, DAVID; GUTIÉRREZ, CARMEN JULIA; SCULLIN, DIANNE
ABSTRACT: Old Hispanic liturgy was practised across much of medieval Iberia until c. 1080. In this article we analyse the extant Old Hispanic processional antiphons, focusing on: the presence or absence of verses; amount of text and relationship with the Bible; cadence placement; number of notes per chant (melodic density) and per syllable; and melodic repetition within and between chants. We demonstrate that the processional antiphons are neither a homogenous corpus nor clearly differentiated stylistically from other Old Hispanic antiphons. In a short case study of the Good Friday Veneration of the Cross, we situate the processional antiphons within their wider ritual context, including their likely staging in the ecclesiastical architecture. As we show, the interaction between melody and ritual directed the antiphon texts towards a particular devotional end.